International Financial Management - Bekaert, Geert; Hodrick, Robert J. (Cambridge University Press, 2018)
This new and fully updated edition of International Financial Management blends theory, data analysis, examples and practical case situations to equip students and business leaders with the analytical tools they need to make informed financial decisions and manage the risks that businesses face in today's competitive global environment. Combining theory and practice, the authors offer the reader a multitude of real-world examples and case studies, emphasising fundamental concepts, principles and analytical theories to enable students to understand not only what to do when confronted with an international financial decision, but why that choice is the correct one. Features include: real data analysis - all fully updated for the third edition; extended cases illustrating practical application of theory; point-counterpoints offering insight into contentious issues; concept boxes that explore and illustrate key concepts; and end-of-chapter questions. Suitable for M.B.A and advanced undergraduate business students taking a course in international financial management or international finance.